a study of the womens collages in usa (Baghdad Science Journal, 2005)
The study aims to identify the colleges women in the USA where he was browsing the Internet for five universities and sixty-two women's college located these colleges in 25 states only three general and other civil 51% supported by the churches and religious associations of various began its founding in Alqrnn eighteenth and continued in the nineteenth and twentieth and to provide an opportunity for women to complete higher education, while most men's colleges opened their doors to the admission of women and turned it on coeducation